Evaluation of hypoglycemic potential of Cuminum cyminum and its role in modulation of cognitive function in rats with induced diabetes - Kumar, Abhishek; Shekhar, Amit; Dua, Mitali; Jangra, Indu; Suranagi, Umesh; Arora, Ekta (Journal of Applied Pharmaceutical Research, 2024)
Background: This study investigated the effects of Cuminum cyminum (C. cyminum) on cognitive behaviour and acetylcholinesterase (AChE) levels in diabetic rats, comparing its efficacy with Glibenclamide, Sulbutiamine, and Resveratrol. Methods: Wistar rats were randomized into 12 groups (n=10) half diabetic and half non-diabetic controls and administered C. cyminum 500 mg/kg and 1000 mg/kg, Glibenclamide (5 mg/kg), Sulbutiamine (50 mg/kg), and Resveratrol (25 mg/kg). Controls included diabetic and non-diabetic rats without treatment. Blood glucose, insulin, oxidative stress markers, and AChE levels were measured, along with behavioural parameters of learning and memory using the elevated plus maze, passive avoidance, and Morris water maze. Results: Both doses of C. cyminum significantly reduced blood glucose levels (Dose I decreased blood glucose levels from 278.5 ± 3.66 mg/dl to 136.8 ± 4.91 mg/dl while dose II decreased the blood glucose levels to 138.8 ± 3.83 mg/dl) and improved learning and memory, as evidenced by faster transfer latency (TL) and better retention in the elevated plus maze and Morris water maze. The higher dose was particularly effective in reducing brain AChE levels and improving cognitive performance in passive avoidance tests. Conclusion: Both doses of C. cyminum decreased the AChE activity induced by diabetes, improving learning and memory. The antioxidant and anti-hyperglycaemic potential may partially contribute to delaying cognitive impairment. Thus, the study suggests that C. cyminum may be beneficial in mitigating behavioural and biochemical changes associated with diabetes mellitus, offering potential as a complementary therapy to existing diabetes treatments. Elaborate studies in the future are essential to explore its antidiabetic and neuroprotective potential.